Economics and climate justice activism: assessing the financial impact of the fossil fuel divestment movement. Issue 4 (2nd October 2022) - Hansen, Tyler; Pollin, Robert
ABSTRACT: Since 2011, climate activists have advanced divestment campaigns against private fossil fuel corporations that aim to inflict damage on fossil fuel corporations through two channels: stigmatizing them and undermining their financial operations. We focus in this paper on this second purpose, considering the extent to which divestment campaigns have succeeded in inflicting financial damage on fossil fuel corporations. We present descriptive data on the level of divested fossil fuel stocks and bonds as well as econometric analysis of the impact of divestment events on the stock market prices of fossil fuel companies. We find that divestment campaigns have not been successful in inflicting significant economic damage on fossil fuel corporations, even though the movement has been successful in mobilizing public opinion against the fossil fuel corporations.